Analysis of Factors Related to the Use of Telemedicine Application Services - Anggre Paramitha Putri; Hermansyah Hermansyah; Asnawi Abdullah; Nurjannah Nurjannah; Hafnidar A. Rani (Indonesian Journal of Global Health Research, 2025)
Telemedicine services can be a diversion of most offline or classic consultations into online consultations through telemedicine services. The use of telemedicine continues, especially through telemedicine services provided by the Ministry of Health for patients who need it, such as about prevention of certain diseases, or patients who have experienced symptoms of certain diseases can consult through telemedicine services. This observational analytical study with a cross-sectional design uses a quantitative approach aimed at analyzing factors related to the level of satisfaction of telemedicine service users in Aceh Province. Data collection used a googleform questionnaire that was distributed using social media for 2 weeks. The sample in the study was the population of Aceh who met the inclusion criteria totaling 468 people. Sampling used the accidental sampling technique. Data analysis used a logistic regression test. factors related to the use of telemedicine application services in Aceh Province are the use of the JKN mobile application (OR=1.61; 95%CI=1.06-2.54; p-value=0.025), income < Minimum Wage (OR=1.64; 95%CI=1.13-2.37; p-value=0.008), and 4G/LTE internet network (OR=1.69; 95%CI=1.01-2.84; p-value=0.046). The most dominant factor related to the use of telemedicine is non-BPJS Kesehatan insurance users (AOR=2.42; 95%CI=0.53 – 11.05). It is expected that respondents should use the telemedicine application counseling facility provided for control and encouragement in supporting and assisting efforts to recover quickly and prevent disease. Respondents also pay attention to the type of application used because each telemedicine application has its own advantages and disadvantages.